Fractographic analyses of zirconia-based fixed partial dentures - (:unkn) unknown (ELSEVIER SCI LTD, 2008)
Objectives. Advances in ceramic processing techniques enable clinicians and ceramists to fabricate all-ceramic fixed partial dentures (FPDs) for posterior regions using high-strength yttria-stabilized tetragonal zirconia polycrystals (Y-TZP). However, failures occur in ceramic FPDs due to their design. The objectives of this study were to determine the site of crack initiation and the causes of fracture in clinically failed zirconia-based ceramic FPDs. Methods. Five clinically failed four-unit Y-TZP-based FPDs (Cercon (R) ceramics, DeguDent GmbH, Hanau, Germany) were retrieved and analyzed. The fragments containing the fracture origins in the veneers (Cercon (R) Ceram S Veneering Ceramic, DeguDent GmbH, Hanau, Germany) of two samples were missing but the rest of veneer structures were present. The other three samples had their veneers intact. Fracture surfaces were examined using fractographic techniques, utilizing both optical and scanning electron microscopes (SEM). Quantitative fractography and fracture mechanics principles were used to estimate the stresses at failure. Results. Primary fractures initiated from the gingival surfaces of connectors at veneer surfaces in four out of the five samples. However, critical flaw sizes could be measured in three of the five cases since fracture origins were lost in the remaining two due to local fragmentation at the crack initiation site. Delaminations between glass veneer and zirconia core were observed in Y-TZP-based FPDs and a secondary fracture initiated from the zirconia core. Secondary fracture controlled the ultimate failure. Failure stresses of the fixed partial dentures that failed due to zirconia fracture ranged from 379 to 501 MPa. Fractures that had origins on the glass veneer surface had failure stresses between 31 and 38 MPa. Significance. Primary fractures in clinically failed Y-TZP-based FPDs initiated from the veneer surfaces. Interfacial delamination in glass veneer/zirconia core bilayer dental ceramic structures controlled the secondary fracture initiation sites and failure stresses in Y-TZP-based fixed partial dentures. (c) 2008 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: dental ceramic; fracture surface analysis; fractography; zirconia; fracture mechanics; FRACTURE-SURFACE-ANALYSIS; MACHINING PROCESS DCM; DENTAL CERAMICS; CONNECTOR DESIGN; BRIDGES; CRACK